Advanced Clinical Generalist Nurse in Nursing Homes -A Qualitative Study of experiences with palliative care for patients with Multimorbidity: A qualitative study of experiences with palliative care for multimorbid patients - Gneist, Juliane; Julnes, Signe Gunn; Mundal, Ingunn Pernille (Nordisk Tidsskrift for Helseforskning, 2026)
Background: The number of patients with multimorbidity in the palliative phase has increased in municipal healthcare. Palliative trajectories can span months or years, requiring continuous follow-up, systematic assessment, and specialized competence. This study explores the experiences of advanced clinical generalist nurses (APN) in palliative care in nursing homes. Method: Qualitative design with semi-structured interviews of eight APN. Data was analyzed using Malterud’s four-step model. Findings: ANP strengthens palliative care for multimorbid patients through systematic mapping, person-centered communication and clinical medication management, increases quality and safety, reduces hospitalizations, but is affected by organizational barriers and unclear roles. Conclusion: APN competence supports holistic palliative care for multimorbid patients through integrated assessment, communication, and medication management. Effective implementation requires clear roles, organizational support, and interdisciplinary collaboration to maximize quality, safety, and continuity of care in nursing homes.
Keywords: advanced clinical nurse; experience; multimorbid; palliative care; nursing homes